EVALUATION OF NATURAL COUMARINS AS POTENTIAL INHIBITORS OF EFFLUX PUMP GENE EXPRESSION IN CARBAPENEM-RESISTANT ACINETOBACTER BAUMANNII FROM RESPIRATORY INFECTION PATIENTS - Rami S. Owaid; Raghda S.M. Al-Omari; Masar J. Al-kurdy (Journal for Technology and Science, 2026)
Objective: This study investigates the potential of natural coumarins to inhibit efflux pump gene expression in carbapenem-resistant strains of Acinetobacter baumannii isolated from respiratory infections. Carbapenem resistance is a growing public health threat, and A. baumannii is a notorious pathogen associated with nosocomial infections. Efflux pumps are one of the mechanisms bacteria employ to develop resistance by actively removing antibiotics from the cell. This study investigates the efficacy of coumarins against certain mechanisms of resistance in certain bacteria. Method: Microtiter plate dilution assays were used to determine the minimum inhibitory concentration (MIC) of the antibiotic meropenem, a member of the class of carbapenems, along with coumarins. The study started from January to June 2023, a total (100) sputum specimens were collected from the Intensive Care Units (ICUs) of hospitals in Diwaniyah. Carbapenem-resistant A. baumannii had four isolates used in the study, each of the six experimental groups. Group 1 was a control and was subjected to a sub-MIC (6.25 µg/mL) of the carbapenem active antibiotic. Group 2 was the control and was subjected to 50 µg/mL of ethidium bromide (EtBr) to confirm the presence of functional efflux pumps. Groups 3 to 6 investigated the interaction of coumarins at a sub-MIC (62.5, 125, 250, and 500 µg/mL) with meropenem. A unique experimental control was used in this study which was real-time quantitative PCR (qPCR) to measure the fold change and the relative expression of two efflux pump genes, adeR and adeB, in all groups. Statistical methods that used were Chi-square at (P < 0.01) and LSD in one way ANOVA method at (P< 0.05) as well as histograms analysis were performed by using GraphPad Prism 7 Statistics software for estimation the difference between means in all groups of the experiment were used. Results: Given both genes had the same fold change in the control group, that change was determined to be 1.0. The corresponding relative changes in control values of the coumarin groups were 0.06 to 0.32 for adeR and 0.25 to 0.66 for adeB which means that both groups in the study were highly over-expressing the genes, exhibiting at least a 2-fold increase in the baseline expression, while the other group (the control) was also exhibiting very high baseline expression. EtBr group’s increase was the most pronounced across the board and in tune with the most upregulation and the function of being an established efflux pump substrate. Statistical comparisons highlighted significant differences between ADEB gene expression in the sub-MIC control and all the coumarin treated groups. Interestingly, for the adeR gene, significant differences were observed only between the control and EtBr groups, not between the control and coumarin-treated groups themselves. Novelty: This study concludes that coumarin treatment at the tested concentrations significantly downregulates the expression of adeR and adeB efflux pump genes in carbapenem-resistant A. baumannii isolates. This downregulation potentially enhances the efficacy of meropenem against these multidrug-resistant bacteria.